2014
DOI: 10.1007/s12665-014-3810-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors responsible for spatial and temporal variation of soil CO2 efflux in a 50 year recovering tropical forest, Peninsular Malaysia

Abstract: Environmental abiotic and biotic factors are important in controlling soil CO2 efflux in forest ecosystems of different ages, as they play an important role in soil respiration. In understanding the spatial and temporal variation of soil CO2 efflux after several years of forest logging, there is a need to quantify the changing soil properties, environmental factors, and the total above and below ground biomass. This study was conducted in a 50-year old recovering tropical lowland forest in Peninsular Malaysia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
8
0
2
Order By: Relevance
“…In this study, the increase in soil respiration was attributed to the change in environmental factors as was observed to be one of the important controlling factors as it was influenced by deforestation activity on the recovering forest [38]. The soil temperature within the period of the study ranged between 24.99 and 25.98 0 C, similar to the study conducted by [34], which stands to alter changes in environmental variables, likewise, soil moisture occurred at a ranged between 20.22 and 25.43%.Furthermore, forest recovering from deforestation could influence the entire environmental factors, which explains the role of deforestation and less dense forest canopy cover as it increases the net radiation on the forest floor to provide a condition to necessitate microorganisms to facilitate soil respiration [33,37].…”
Section: 1monthly Pattern Of Soil Respiration Rate and Effects Of Esupporting
confidence: 71%
See 2 more Smart Citations
“…In this study, the increase in soil respiration was attributed to the change in environmental factors as was observed to be one of the important controlling factors as it was influenced by deforestation activity on the recovering forest [38]. The soil temperature within the period of the study ranged between 24.99 and 25.98 0 C, similar to the study conducted by [34], which stands to alter changes in environmental variables, likewise, soil moisture occurred at a ranged between 20.22 and 25.43%.Furthermore, forest recovering from deforestation could influence the entire environmental factors, which explains the role of deforestation and less dense forest canopy cover as it increases the net radiation on the forest floor to provide a condition to necessitate microorganisms to facilitate soil respiration [33,37].…”
Section: 1monthly Pattern Of Soil Respiration Rate and Effects Of Esupporting
confidence: 71%
“…There wasa steady decrease in efflux rate between August and November at an average mean of 340.30, 308.12, 286.07 and 256.05 mg m -2 h -1 , respectively, much lower than Pasoh forest reserve lowland Peninsular [34,35], which was strongly influenced by the availability of soil moisture and was significant correlated (p<0.05). Our finding revealed that monthly variation in soil respiration was influenced by both soil temperature and moisture as was also reported by [36].The rise and decrease in soil respiration for the period of measurement was recorded to be parallel to soil temperature and soil moisture which indicated soil respiration had positively and significantly correlation with both soil temperature and moisture (p<0.05).…”
Section: 1monthly Pattern Of Soil Respiration Rate and Effects Of Ementioning
confidence: 89%
See 1 more Smart Citation
“…The duration of the study represents the three seasons of the tropics (post-monsoon, pre-monsoon and monsoon period). reduce the build-up of pressure on the soil interphase, and monitored with a barometer [11]. The infrared gas analyser was calibrated in the laboratory using CO 2 as zero standards (1,000 g).…”
Section: Site Descriptionmentioning
confidence: 99%
“…As a result of this logging, quantifying the associated environmental factors to influence soil CO 2 efflux is the key to estimate the soil CO 2 efflux rate. The mechanistic links of logging activity, environmental factors, soil properties and soil CO 2 efflux are poorly understood under the tropical deforested tropical forest [11], and the important step is to determine their interactive links and effect.…”
Section: Introductionmentioning
confidence: 99%